GIS-Multicriteria Analysis Using AHP to Evaluate the Landslide Risk in Road Lifelines - Giovanni Leonardi; Rocco Palamara; Francesco Manti; Antonio Tufano (Applied Sciences, 2022)
The present paper proposes a new methodology to characterize the landslide susceptibility of the Reggio Calabria metropolitan area. For this purpose, various factors were used, such as land use, slope, rainfall, elevation, lithology, distance from roads and rivers, and thanks to the use of GIS devices and the AHP method, the landslide risk was defined for the whole territory. The values obtained were classified into four categories: low, moderate, high, and very high. They were then exported into the GIS environment to produce a landslide susceptibility map. The study carried out demonstrates the fragility of the Calabrian territory. From the results obtained, in fact, 66% of the metropolitan territory of Reggio Calabria appears to have a medium–high landslide risk.